Combination of Rapamycin and MK-2206 Induced Cell Death via Autophagy and Necroptosis in MYCN-Amplified Neuroblastoma Cell Lines - Dong, Yudi; Gong, Wei; Hua, Zhongyan; Chen, Bo; Zhao, Guifeng; Liu, Zhihui; Thiele, Carol J.; Li, Zhijie (Frontiers in Pharmacology, 2020)
Abstract Neuroblastoma (NB) is the most common pediatric malignant extracranial solid tumor. Despite multi-modality therapies, the emergence of drug resistance is an obstacle in the treatment of high-risk neuroblastoma patients (with MYCN amplification). In our previous study, we found that rapamycin and MK-2206 synergistically induced cell death in MYCN-amplified cell lines but the mechanisms remained unclear. In our present study, either 3-MA or necroatatin-1 blocked the cell death induced by rapamycin and MK-2206, but z-VAD-fmk did not block this cell death. The expressions of autophagy markers (ATG5, ATG7, Beclin-1, LC3 B) and the necroptosis marker RIPK3 increased and another necroptosis marker RIPK1 decreased after the combination treatment of rapamycin and MK-2206, and were accompanied by the morphological characteristics of autophagy and necroptosis. In NB xenograft tumor tissues, the expressions of autophagy and necroptosis markers were consistent with observations in vitro. These data suggested that autophagy and necroptosis contributed to the cell death induced by rapamycin and MK-2206 in NB cells. To understand the role of MYCN in this process, MYCN expression was downregulated in MYCN-amplified cell lines (NGP, BE2) using siRNAs and was upregulated in MYCN non-amplified cell lines (AS, SY5Y) using plasmid. We found the cell death induced by rapamycin and MK-2206 was MYCN-dependent. We also found that the metabolic activity in NB cells was correlated with the expression level of MYCN. This study delineates the role of MYCN in the cell death induced by combination treatment of rapamycin and MK-2206 in MYCN-amplified NB cells.